The effect of cognitive emotion regulation on direct-acting antivirals adherence in patients with hepatitis C - Turcu-Stiolica, Adina; Doica, Irina Paula; Ungureanu, Bogdan Silviu; Subtirelu, Mihaela-Simona; Florescu, Dan Nicolae; Turcu-Stiolica, Razvan-Aurelian; Rogoveanu, Ion; Gheonea, Dan-Ionut (Frontiers in Pharmacology, 2024)
Adherence to direct-acting antivirals (DAAs) could be a predictor of chronic viral hepatitis C (HCV) therapeutic failure. We examined the perceptions of patients receiving DAAs to determine how cognitive factors influence their decision to maintain adherence. Also, we explored the threshold of DAAs adherence for obtaining sustained virologic response (SVR) among patients with HCV, in order to better implement a strategy that improves the DAAs adherence in the future clinical practice.Methods: A single-arm prospective study was performed. Patients with HCV that started and completed DAAs treatment in the County Hospital of Craiova, Dolj, Romania, were enrolled. Patients' medication adherence was assessed using the HCV-AD10 questionnaire, and the cognitive emotion regulation was measured with CERQ questionnaire (five positive/adaptive cognitive emotion-regulation domains and four negative/maladaptive domains). Spearman correlation analysis was conducted to explore the relationships between adherence and different factors. ROC-curves were used to evaluate the adherence threshold to achieve SVR. A linear regression model was performed to analyze the primary outcome (DAAs adherence) to be the target variable based on given independent variables (age, treatment duration, severity of HCV, the nine adaptive and maladaptive strategies).Results: 368 patients (mean age: 61 years) with HCV diagnosed 4.05±6.38 (average) years ago were enrolled. Mean (±SD) adherence via HCV-AD10 was 91.51±8.34, and the proportion of the participants achieving SVR was 96%. Patients with an adherence less than 84% (5 patients, 1.36%) was considered nonadherent and they have a high probability of not achieving response (sensitivity and specificity of 83% and 80%, respectively). We obtained significantly higher values of three adaptive strategies between adherent and nonadherent patients following DAAs treatment: in positive refocusing (p-value = 0.044), refocus on planning (p-value = 0.037), and positive reappraisal (p-value = 0.047).Discussion: The interplay between the three adaptive strategies of the cognitive emotion regulation and the enhancement of DAAs adherence contributes to a more holistic comprehension of patient behavior in the context of HCV treatment. Increasing refocusing and planning using goal setting and assisting patients in establishing specific, achievable goals can be crucial strategies for clinicians aiming to improve adherence among their patients.